Preparation method of anti-aging ABS (Acrylonitrile Butadiene Styrene) resin

The described method for preparing ABS resin addresses thermal degradation and mechanical property loss by pretreating monomers, using nanofillers and stabilizers, and melt blending, resulting in enhanced mechanical and thermal stability for varied applications.

CN119177003AInactive Publication Date: 2024-12-24SHENZHEN HUAYUN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411258836.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for preparing ABS resin fail to adequately address thermal degradation and mechanical property loss, limiting its application in high-demand environments and outdoor settings.

Method used

A method involving pretreatment of styrene, acrylonitrile, and butadiene monomers, followed by free radical emulsion copolymerization, surface treatment with nanofillers and stabilizers, and melt blending using a twin-screw extruder to create an aging-resistant ABS resin.

Benefits of technology

The method enhances mechanical properties and thermal stability, preventing thermal degradation and improving uniformity and stability, making it suitable for diverse applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177003A_ABST
    Figure CN119177003A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of anti-aging ABS (Acrylonitrile Butadiene Styrene) resin, and belongs to the technical field of ABS resin production.The preparation method comprises the following specific steps: S1, pretreating raw materials and preparing an ABS resin matrix; s2, carrying out blending modification on the ABS resin matrix; s3, carrying out surface treatment on the blended ABS resin; s4, performance testing, packaging and storing; according to the present invention, the thermal degradation is effectively prevented, the mechanical property and the thermal stability of the ABS resin are enhanced, the uniformity and the stability of the ABS resin are further improved, different application requirements are met, and the comprehensive performance improvement is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ABS resin production, and in particular to a method for preparing aging-resistant ABS resin. Background Art

[0002] ABS resin is a widely used thermoplastic. Due to its excellent mechanical properties, excellent processability, low cost and good surface gloss, it is widely used in automotive parts, household appliances, electronic products and consumer products. ABS resin has good impact resistance, heat resistance and dimensional stability. However, the environmental factors it faces during long-term use will cause the degradation of its physical and chemical properties. This phenomenon is called material aging. The aging process will cause a series of adverse changes in ABS resin, including surface cracking, discoloration, strength loss and toughness loss. These changes limit the application of ABS resin in certain high-demand environments, especially in outdoor applications and long-term exposure to sunlight. Therefore, in order to solve these problems, it is particularly important to invent a method for preparing aging-resistant ABS resin.

[0003] After searching, Chinese patent number CN201810329445.2 discloses a method for preparing a new aging-resistant ABS resin material. Although it effectively improves the heat resistance, light resistance and aging resistance of ABS, it cannot prevent thermal degradation. The mechanical properties and thermal stability of ABS resin are low, and it cannot adapt to the needs of different applications. Summary of the invention

[0004] The purpose of the present invention is to solve the defects in the prior art and to propose a method for preparing an aging-resistant ABS resin.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing an aging-resistant ABS resin, wherein the aging-resistant ABS resin is composed of the following raw materials in parts by weight: 40-60 parts of styrene, 20-40 parts of acrylonitrile, 10-20 parts of butadiene, 1-5 parts of nanofiller, 3-10 parts of maleic anhydride grafted polyethylene, 0.5-2 parts of hindered phenol antioxidant, 0.5-1.5 parts of hindered amine light stabilizer, 0.1-1 parts of silane coupling agent solution and 0.5-2 parts of potassium persulfate solution; The specific steps of the preparation method of the aging-resistant ABS resin are as follows: S1. Pretreating raw materials and preparing ABS resin matrix: pretreating styrene, acrylonitrile and butadiene monomers, and adding styrene, acrylonitrile and butadiene into a reaction kettle according to a ratio under the protection of inert gas, and performing free radical emulsion copolymerization to obtain ABS resin matrix; S2. Blending and modifying the ABS resin matrix: surface treating the nanofiller with a silane coupling agent, and melt-blending the treated nanofiller and maleic anhydride grafted polyethylene with the ABS resin matrix using a twin-screw extruder; S3, performing surface treatment on the blended ABS resin: adding a hindered phenol antioxidant and a hindered amine light stabilizer to the blended ABS resin, and then performing surface treatment on the ABS resin; S4. Performance testing, packaging and storage: The treated ABS resin is extruded through a melt extruder and pelletized to obtain resin particles. The particles are tested for mechanical properties, thermal stability and aging resistance, and quality control and adjustment are carried out based on the test results. After passing the test, they are packaged and stored according to specifications.

[0006] As a further solution of the present invention, the specific steps of pre-treating the monomers of styrene, acrylonitrile and butadiene in S1 are as follows: P1.1: Add the styrene raw material into the distillation kettle and slowly heat it to the boiling point of styrene to evaporate the low-boiling impurities. The evaporated gas then enters the fractionation column. Through the efficient separation effect of the fractionation column, the low-boiling impurities are condensed and collected at the top and treated as waste; P1.2: When the temperature in the still reaches the boiling point of styrene, styrene enters the middle section of the fractionation column in gaseous form, and then condenses and collects high-purity styrene liquid in the condenser, and the remaining high-boiling impurities in the still are regularly discharged or processed; P1.3: Preheat the acrylonitrile raw material at 40 to 60°C and remove the moisture therein by continuous stirring. Use a dryer equipped with 3A molecular sieve to absorb the trace moisture in the pretreated acrylonitrile. Use a distillation column to separate acrylonitrile, unsaturated compounds and high-boiling impurities by using the difference in boiling points. Collect and store the distilled acrylonitrile. P1.4: Place butadiene in a freeze dryer and adjust the internal temperature of the freeze dryer to -30℃ to -40℃ to precipitate the water in the butadiene in the form of ice. Set the internal pressure of the freeze dryer to 0.1Pa to 100Pa to sublime the ice. Perform deep dehydration treatment on the freeze-dried butadiene by using 4A molecular sieve. Then place the butadiene in a sealed container and circulate inert gas to replace excess oxygen in the container until the oxygen content drops below the ppm level.

[0007] As a further embodiment of the present invention, the specific steps of the free radical emulsion copolymerization reaction described in S1 are as follows: P2.1: Clean and dry the inside of the reactor, then add 150-300 parts of deionized water into the reactor, and slowly add 0.5-5 parts of polyoxyethylene alkyl ether emulsifier solution into the deionized water, then start the stirring system of the reactor, stir at a speed of 200-500rpm for 10-20 minutes, so that the polyoxyethylene alkyl ether emulsifier is fully dissolved and evenly distributed in the water phase to form a uniform water phase system; P2.2: According to the formula ratio, weigh the pretreated styrene, acrylonitrile and butadiene respectively, and slowly add each monomer into the prepared aqueous phase in the order of styrene, acrylonitrile and butadiene. Then slowly add the potassium persulfate solution into the reactor and continue stirring at a speed of 300-600rpm for 20-30 minutes until the mixture is evenly mixed. P2.3: gradually raise the temperature in the reactor to 60-85°C at a rate of 1-2°C per minute, and adjust the stirring speed of the reactor to 400-800rpm. Continue the reaction for 3-6 hours. During the reaction, take samples regularly for analysis to monitor the conversion rate of the monomer and the molecular weight of the copolymer. P2.4: When the reaction reaches more than 90%, stop heating and gradually cool the reactor to room temperature. After the reaction is completed, open the reactor, use a filter to unload the reaction product, separate the unreacted monomers and impurities to obtain a preliminary purified copolymer emulsion, and then remove excess emulsifier and residual monomers by evaporation or solvent extraction to obtain the ABS resin matrix.

[0008] As a further solution of the present invention, the nanofiller in S2 is specifically nano-silicon dioxide, nano-calcium carbonate, nano-clay or carbon nanotube.

[0009] As a further embodiment of the present invention, the specific steps of melt blending described in S2 are as follows: P3.1: Dry the nanofiller at 80-100°C for 4-6 hours, then add the dried nanofiller to the silane coupling agent solution, stir at 50-70°C for 1-2 hours until the mixture is uniformly stirred, and then dry at 120-150°C for 2-4 hours to obtain the surface-treated nanofiller; P3.2: Weigh the treated nanofiller and maleic anhydride grafted polyethylene according to the formula ratio of 5-20% nanofiller to 80-95% maleic anhydride grafted polyethylene, and then pre-mix the treated nanofiller and maleic anhydride grafted polyethylene in a low-speed mixer or high-speed mixer for 10-15 minutes; P3.3: Start the twin-screw extruder and preheat it to 180-220℃. When the temperature of the equipment is stable, add the premix to the feed port and add the ABS resin matrix at a formula ratio of 70-95%. Then the premix and ABS resin are heated and melted in the twin-screw extruder at the same time. P3.4: The twin-screw extruder screw blends the molten premix with the ABS resin matrix at a speed of 100-300rpm for 2-5 minutes until a uniform composite material is formed. The molten composite material is then extruded through the extrusion die of the equipment, cooled to room temperature by air cooling or water bath, and then pelletized by a pelletizer to obtain the final ABS resin particles.

[0010] As a further solution of the present invention, the specific steps of surface treatment of ABS resin in S3 are as follows: P4.1: Weigh 0.1-0.5% of the mass of ABS resin as hindered phenol antioxidant, and weigh 0.2-1.0% of the mass of ABS resin as hindered amine light stabilizer, and then put the hindered phenol antioxidant, hindered amine light stabilizer and ABS resin particles into a high-speed mixer; P4.2: Mix the hindered phenol antioxidant, the hindered amine light stabilizer and the ABS resin particles by a high-speed mixer at a speed of 1000-3000 rpm for 10-15 minutes. After the mixing is completed, preheat the ABS resin particles to which the hindered phenol antioxidant and the hindered amine light stabilizer are added to 50-80°C; P4.3: Evenly cover the surface of the preheated ABS resin particles with a surface treatment agent of 1-3% by spraying or dipping for 5-10 minutes, and dry the surface-treated ABS resin particles at a temperature of 80-120°C for 1-2 hours.

[0011] Compared with the prior art, the present invention has the following beneficial effects: The present invention pre-treats styrene, acrylonitrile and butadiene to remove impurities and moisture in each monomer, adds the pre-treated styrene, acrylonitrile and butadiene into a reaction kettle according to a ratio under the protection of inert gas, then adds potassium sulfate solution, and performs free radical emulsion copolymerization at a temperature of 60-80°C for 4-8 hours to obtain an ABS resin matrix, performs surface treatment on a nano filler through a silane coupling agent solution, weighs the treated nano filler and maleic anhydride grafted polyethylene, and then pre-mixes the treated nano filler and maleic anhydride grafted polyethylene in a low-speed mixer or a high-speed mixer for 10-15 minutes, starts a twin-screw extruder, and preheats the interior thereof to 180-220°C, adds the premix to a feed port when the temperature of the equipment is stable, and simultaneously adds the ABS resin matrix. The premix and the ABS resin are heated and melted in a twin-screw extruder at the same time. The twin-screw extruder screw blends the molten premix with the ABS resin matrix for 2-5 minutes at a speed of 100-300rpm until a uniform composite material is formed. The molten composite material is extruded through an extrusion die of the equipment, and then cooled to room temperature by air cooling or a water bath, and then pelletized by a pelletizer to obtain final ABS resin particles. The hindered phenol antioxidant, the hindered amine light stabilizer and the ABS resin particles are put into a high-speed mixer for mixing, and the surface of the mixed ABS resin particles is treated to effectively prevent thermal degradation, enhance the mechanical properties and thermal stability of the ABS resin, further improve the uniformity and stability of the ABS resin, and adapt to the needs of different applications to provide more comprehensive performance improvement. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0013] Figure 1 The present invention provides a schematic diagram of the preparation process of an aging-resistant ABS resin. DETAILED DESCRIPTION

[0014] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Example

[0015] See also Figure 1 The present invention provides a technical solution: a method for preparing an aging-resistant ABS resin, and the specific steps of the method for preparing an aging-resistant ABS resin are as follows: Step 1: Add 50 parts of styrene raw material into the distillation kettle and slowly heat it to the boiling point of styrene to evaporate the low-boiling impurities. Then the evaporated gas enters the distillation column, and through the efficient separation of the distillation column, the low-boiling impurities are condensed and collected at the top and treated as waste. When the temperature in the distillation kettle reaches the boiling point of styrene, styrene enters the middle section of the distillation column in gaseous form, and then condenses and collects high-purity styrene liquid in the condenser, and regularly discharges or treats the high-boiling impurities remaining in the distillation kettle. Preheat 30 parts of acrylonitrile raw material at 40 to 60°C, remove moisture through continuous stirring, and adsorb the pretreated styrene through a dryer equipped with 3A molecular sieve. The trace moisture in acrylonitrile is removed, and acrylonitrile, unsaturated compounds and high-boiling impurities are separated by a distillation column using the difference in boiling points. At the same time, the distilled acrylonitrile is collected and stored. 20 parts of butadiene are placed in a freeze dryer, and the internal temperature of the freeze dryer is adjusted to -30°C to -40°C to precipitate the moisture in the butadiene in the form of ice, and the internal pressure of the freeze dryer is set at 0.1Pa to 100Pa to sublime the ice. The freeze-dried butadiene is deeply dehydrated by using a 4A molecular sieve, and then the butadiene is placed in a sealed container, and an inert gas is circulated to replace the excess oxygen in the container until the oxygen content drops below the ppm level.

[0016] Step 2: Clean and dry the inside of the reactor, then add 200 parts of deionized water into the reactor, and slowly add 1 part of the polyoxyethylene alkyl ether emulsifier solution into the deionized water, then start the stirring system of the reactor, stir at a speed of 200-500rpm for 10-20 minutes, so that the polyoxyethylene alkyl ether emulsifier is fully dissolved and evenly distributed in the water phase to form a uniform water phase system, weigh the pretreated styrene, acrylonitrile and butadiene respectively according to the formula ratio, and slowly add each monomer to the prepared water phase one by one in the order of styrene, acrylonitrile and butadiene, then slowly add 0.5 parts of potassium persulfate solution into the reactor, and stir at a speed of 300-600rpm. degree, continue stirring for 20-30 minutes until the mixture is uniformly mixed, gradually increase the temperature in the reactor to 60-85°C at a rate of 1-2°C per minute, adjust the stirring speed of the reactor to 400-800rpm, and continue the reaction for 3-6 hours. During the reaction, regularly take samples for analysis to monitor the conversion rate of the monomer and the molecular weight of the copolymer. When the reaction reaches more than 90%, stop heating and gradually cool the reactor to room temperature. After the reaction is completed, open the reactor, use a filter to discharge the reaction product, separate the unreacted monomer and impurities to obtain a preliminarily purified copolymer emulsion, and then remove the excess emulsifier and residual monomer by evaporation or solvent extraction to obtain an ABS resin matrix.

[0017] Step 3: Dry 5 parts of nanofillers at 80-100°C for 4-6 hours, then add the dried nanofillers to 1 part of silane coupling agent solution, stir at 50-70°C for 1-2 hours until the mixture is uniformly stirred, and then dry at 120-150°C for 2-4 hours to obtain the surface-treated nanofillers, and then premix the treated nanofillers with 15 parts of maleic anhydride grafted polyethylene in a low-speed mixer or high-speed mixer for 10-15 minutes, start the twin-screw extruder, and preheat the interior to 180-220°C. When the temperature of the equipment is stable, add the premix to the feed port, and at the same time add the ABS resin matrix at a formula ratio of 70-95%. Then the premix and the ABS resin are heated and melted in the twin-screw extruder at the same time. The twin-screw extruder screw blends the molten premix with the ABS resin matrix at a speed of 100-300rpm for 2-5 minutes until a uniform composite material is formed. The molten blended composite material is then extruded through the extrusion die of the equipment, cooled to room temperature by air cooling or water bath, and then pelletized by a pelletizer to obtain the final ABS resin particles.

[0018] The nanofiller is specifically nano-silicon dioxide, nano-calcium carbonate, nano-clay or carbon nanotube.

[0019] Step 4: prepare 0.3 parts of hindered phenol antioxidant and 0.5 parts of hindered amine light stabilizer, then put the hindered phenol antioxidant, hindered amine light stabilizer and ABS resin particles into a high-speed mixer, mix the hindered phenol antioxidant, hindered amine light stabilizer and ABS resin particles at a speed of 1000-3000rpm through the high-speed mixer for 10-15 minutes, after the mixing is completed, preheat the ABS resin particles with the hindered phenol antioxidant and hindered amine light stabilizer added to 50-80℃, and evenly cover the surface of the preheated ABS resin particles with a surface treatment agent of 1-3% by spraying or dipping for 5-10 minutes, and dry the surface-treated ABS resin particles at a temperature of 80-120℃ for 1-2 hours. Example

[0020] See also Figure 1 The present invention provides a technical solution: a method for preparing an aging-resistant ABS resin, a method for preparing an aging-resistant ABS resin, and the specific steps of the method for preparing an aging-resistant ABS resin are as follows: Step 1: Add 60 parts of styrene raw material into the distillation kettle and slowly heat it to the boiling point of styrene to evaporate the low-boiling impurities. Then the evaporated gas enters the distillation column, and through the efficient separation of the distillation column, the low-boiling impurities are condensed and collected at the top and treated as waste. When the temperature in the distillation kettle reaches the boiling point of styrene, styrene enters the middle section of the distillation column in gaseous form, and then condenses and collects high-purity styrene liquid in the condenser, and regularly discharges or treats the high-boiling impurities remaining in the distillation kettle. Preheat 25 parts of acrylonitrile raw material at 40 to 60°C, remove moisture through continuous stirring, and adsorb the pretreated styrene through a dryer equipped with 3A molecular sieve. The trace amount of water in acrylonitrile is removed, and acrylonitrile, unsaturated compounds and high-boiling impurities are separated by a distillation column using the difference in boiling points. At the same time, the distilled acrylonitrile is collected and stored. 15 parts of butadiene are placed in a freeze dryer, and the internal temperature of the freeze dryer is adjusted to -30°C to -40°C to precipitate the water in the butadiene in the form of ice, and the internal pressure of the freeze dryer is set at 0.1Pa to 100Pa to sublime the ice. The freeze-dried butadiene is deeply dehydrated by using a 4A molecular sieve, and then the butadiene is placed in a sealed container, and an inert gas is circulated to replace the excess oxygen in the container until the oxygen content drops below the ppm level.

[0021] Step 2: Clean and dry the inside of the reactor, then add 250 parts of deionized water into the reactor, and slowly add 1.2 parts of polyoxyethylene alkyl ether emulsifier solution into the deionized water, then start the stirring system of the reactor, stir at a speed of 200-500rpm for 10-20 minutes to fully dissolve the polyoxyethylene alkyl ether emulsifier and evenly distribute it in the water phase to form a uniform water phase system, weigh the pretreated styrene, acrylonitrile and butadiene respectively according to the formula ratio, and slowly add each monomer to the prepared water phase one by one in the order of styrene, acrylonitrile and butadiene, then slowly add 0.6 parts of potassium persulfate solution into the reactor, and stir at 300-600rpm. speed, continue stirring for 20-30 minutes until the mixture is evenly mixed, gradually increase the temperature in the reactor to 60-85°C at a rate of 1-2°C per minute, and adjust the stirring speed of the reactor to 400-800rpm, continue the reaction for 3-6 hours, and during the reaction, regularly take samples for analysis to monitor the conversion rate of the monomer and the molecular weight of the copolymer. When the reaction reaches more than 90%, stop heating and gradually cool the reactor to room temperature. After the reaction is completed, open the reactor, use a filter to discharge the reaction product, separate the unreacted monomer and impurities to obtain a preliminarily purified copolymer emulsion, and then remove excess emulsifier and residual monomer by evaporation or solvent extraction to obtain an ABS resin matrix.

[0022] Step 3: Dry 6 parts of nanofillers at 80-100°C for 4-6 hours, then add the dried nanofillers to 1.2 parts of silane coupling agent solution, stir at 50-70°C for 1-2 hours until the mixture is uniformly stirred, and then dry at 120-150°C for 2-4 hours to obtain the surface-treated nanofillers, and then premix the treated nanofillers with 20 parts of maleic anhydride grafted polyethylene in a low-speed mixer or high-speed mixer for 10-15 minutes, start the twin-screw extruder, and preheat the interior to 180-220°C. When the temperature of the equipment is stable, add the premix to the feed port, and at the same time add the ABS resin matrix at a formula ratio of 70-95%. Then the premix and the ABS resin are heated and melted in the twin-screw extruder at the same time. The twin-screw extruder screw blends the molten premix with the ABS resin matrix at a speed of 100-300rpm for 2-5 minutes until a uniform composite material is formed. The molten blended composite material is then extruded through the extrusion die of the equipment, cooled to room temperature by air cooling or water bath, and then pelletized by a pelletizer to obtain the final ABS resin particles.

[0023] The nanofiller is specifically nano-silicon dioxide, nano-calcium carbonate, nano-clay or carbon nanotube.

[0024] Step 4: prepare 0.4 parts of hindered phenol antioxidant and 0.7 parts of hindered amine light stabilizer, then put the hindered phenol antioxidant, hindered amine light stabilizer and ABS resin particles into a high-speed mixer, mix the hindered phenol antioxidant, hindered amine light stabilizer and ABS resin particles at a speed of 1000-3000rpm through the high-speed mixer for 10-15 minutes, after the mixing is completed, preheat the ABS resin particles with the hindered phenol antioxidant and hindered amine light stabilizer added to 50-80℃, spray or immerse for 5-10 minutes, evenly cover the surface of the preheated ABS resin particles with a surface treatment agent of 1-3% concentration, and dry the surface-treated ABS resin particles at a temperature of 80-120℃ for 1-2 hours. Example

[0025] See also Figure 1 The present invention provides a technical solution: a method for preparing an aging-resistant ABS resin, a method for preparing an aging-resistant ABS resin, and the specific steps of the method for preparing an aging-resistant ABS resin are as follows: Step 1: Add 55 parts of styrene raw material into the distillation kettle, slowly heat it to the boiling point of styrene to evaporate the low-boiling impurities, and then the evaporated gas enters the distillation column, and through the efficient separation of the distillation column, the low-boiling impurities are condensed and collected at the top and treated as waste. When the temperature in the distillation kettle reaches the boiling point of styrene, styrene enters the middle section of the distillation column in gaseous form, and then condenses and collects high-purity styrene liquid in the condenser, and regularly discharges or treats the high-boiling impurities remaining in the distillation kettle. Preheat 35 parts of acrylonitrile raw material at 40 to 60°C, remove moisture through continuous stirring, and adsorb the pretreated styrene through a dryer equipped with 3A molecular sieve. The trace amount of water in acrylonitrile is removed, and acrylonitrile, unsaturated compounds and high-boiling impurities are separated by a distillation column using the difference in boiling points. At the same time, the distilled acrylonitrile is collected and stored. 15 parts of butadiene are placed in a freeze dryer, and the internal temperature of the freeze dryer is adjusted to -30°C to -40°C to precipitate the water in the butadiene in the form of ice, and the internal pressure of the freeze dryer is set at 0.1Pa to 100Pa to sublime the ice. The freeze-dried butadiene is deeply dehydrated by using a 4A molecular sieve, and then the butadiene is placed in a sealed container, and an inert gas is circulated to replace the excess oxygen in the container until the oxygen content drops below the ppm level.

[0026] Step 2: Clean and dry the inside of the reactor, then add 220 parts of deionized water into the reactor, and slowly add 1 part of the polyoxyethylene alkyl ether emulsifier solution into the deionized water, then start the stirring system of the reactor, stir at a speed of 200-500rpm for 10-20 minutes, so that the polyoxyethylene alkyl ether emulsifier is fully dissolved and evenly distributed in the water phase to form a uniform water phase system, weigh the pretreated styrene, acrylonitrile and butadiene respectively according to the formula ratio, and slowly add each monomer to the prepared water phase one by one in the order of styrene, acrylonitrile and butadiene, then slowly add 0.4 parts of potassium persulfate solution into the reactor, and stir at a speed of 300-600rpm. degree, continue stirring for 20-30 minutes until the mixture is uniformly mixed, gradually increase the temperature in the reactor to 60-85°C at a rate of 1-2°C per minute, adjust the stirring speed of the reactor to 400-800rpm, and continue the reaction for 3-6 hours. During the reaction, regularly take samples for analysis to monitor the conversion rate of the monomer and the molecular weight of the copolymer. When the reaction reaches more than 90%, stop heating and gradually cool the reactor to room temperature. After the reaction is completed, open the reactor, use a filter to discharge the reaction product, separate the unreacted monomer and impurities to obtain a preliminarily purified copolymer emulsion, and then remove the excess emulsifier and residual monomer by evaporation or solvent extraction to obtain an ABS resin matrix.

[0027] Step 3: Dry 4 parts of nanofillers at 80-100°C for 4-6 hours, then add the dried nanofillers to 1 part of silane coupling agent solution, stir at 50-70°C for 1-2 hours until the mixture is uniformly stirred, and then dry at 120-150°C for 2-4 hours to obtain the surface-treated nanofillers, and then premix the treated nanofillers with 18 parts of maleic anhydride grafted polyethylene in a low-speed mixer or high-speed mixer for 10-15 minutes, start the twin-screw extruder, and preheat the interior to 180-220°C. When the temperature of the equipment is stable, add the premix to the feed port, and at the same time add the ABS resin matrix at a formula ratio of 70-95%. Then the premix and the ABS resin are heated and melted in the twin-screw extruder at the same time. The twin-screw extruder screw blends the molten premix with the ABS resin matrix at a speed of 100-300rpm for 2-5 minutes until a uniform composite material is formed. The molten blended composite material is then extruded through the extrusion die of the equipment, cooled to room temperature by air cooling or water bath, and then pelletized by a pelletizer to obtain the final ABS resin particles.

[0028] The nanofiller is specifically nano-silicon dioxide, nano-calcium carbonate, nano-clay or carbon nanotube.

[0029] Step 4: prepare 0.5 parts of hindered phenol antioxidant and 0.6 parts of hindered amine light stabilizer, then put the hindered phenol antioxidant, hindered amine light stabilizer and ABS resin particles into a high-speed mixer, mix the hindered phenol antioxidant, hindered amine light stabilizer and ABS resin particles at a speed of 1000-3000rpm through the high-speed mixer for 10-15 minutes, after the mixing is completed, preheat the ABS resin particles with the hindered phenol antioxidant and hindered amine light stabilizer added to 50-80℃, spray or immerse for 5-10 minutes, evenly cover the surface of the preheated ABS resin particles with a surface treatment agent of 1-3% concentration, and dry the surface-treated ABS resin particles at a temperature of 80-120℃ for 1-2 hours.

[0030] This comparative example is an ABS resin prepared by a preparation method of a new aging-resistant ABS resin material disclosed in Chinese Patent No. CN202010289789.2.

[0031] By comparison, it can be seen that the ABS resins prepared in Examples 1, 2 and 3 have comparable performance to the ABS resin prepared in Comparative Example 1. At the same time, the ABS resins prepared in Examples 1, 2 and 3 effectively prevent thermal degradation, enhance the mechanical properties and thermal stability of the ABS resin, use a twin-screw extruder for melt extrusion, and then use cold water stranding for granulation to further improve the uniformity and stability of the ABS resin, and meet the needs of different applications, providing more comprehensive performance improvements.

[0032] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing aging-resistant ABS resin, characterized in that: The aging-resistant ABS resin is composed of the following raw materials in parts by weight: 40-60 parts of styrene, 20-40 parts of acrylonitrile, 10-20 parts of butadiene, 1-5 parts of nano filler, 3-10 parts of maleic anhydride grafted polyethylene, 0.5-2 parts of hindered phenol antioxidant, 0.5-1.5 parts of hindered amine light stabilizer, 0.1-1 parts of silane coupling agent solution and 0.5-2 parts of potassium persulfate solution; The specific steps of the preparation method of the aging-resistant ABS resin are as follows: S1. Pretreating raw materials and preparing ABS resin matrix: pretreating styrene, acrylonitrile and butadiene monomers, and adding styrene, acrylonitrile and butadiene into a reaction kettle according to a ratio under the protection of inert gas, and performing free radical emulsion copolymerization to obtain ABS resin matrix; S2. Blending and modifying the ABS resin matrix: surface treating the nanofiller with a silane coupling agent, and melt-blending the treated nanofiller and maleic anhydride grafted polyethylene with the ABS resin matrix using a twin-screw extruder; S3, performing surface treatment on the blended ABS resin: adding a hindered phenol antioxidant and a hindered amine light stabilizer to the blended ABS resin, and then performing surface treatment on the ABS resin; S4. Performance testing, packaging and storage: The treated ABS resin is extruded through a melt extruder and pelletized to obtain resin particles. The particles are tested for mechanical properties, thermal stability and aging resistance, and quality control and adjustment are carried out based on the test results. After passing the test, they are packaged and stored according to specifications.

2. The method for preparing an aging-resistant ABS resin according to claim 1, characterized in that: The specific steps of pre-treating styrene, acrylonitrile and butadiene monomers in S1 are as follows: P1.1: Add the styrene raw material into the distillation kettle and slowly heat it to the boiling point of styrene to evaporate the low-boiling impurities. The evaporated gas then enters the fractionation column. Through the efficient separation effect of the fractionation column, the low-boiling impurities are condensed and collected at the top and treated as waste; P1.2: When the temperature in the still reaches the boiling point of styrene, styrene enters the middle section of the fractionation column in gaseous form, and then condenses and collects high-purity styrene liquid in the condenser, and the remaining high-boiling impurities in the still are regularly discharged or processed; P1.3: Preheat the acrylonitrile raw material at 40 to 60°C and remove the moisture therein by continuous stirring. Use a dryer equipped with 3A molecular sieve to absorb the trace moisture in the pretreated acrylonitrile. Use a distillation column to separate acrylonitrile, unsaturated compounds and high-boiling impurities by using the difference in boiling points. Collect and store the distilled acrylonitrile. P1.4: Place butadiene in a freeze dryer and adjust the internal temperature of the freeze dryer to -30℃ to -40℃ to precipitate the water in the butadiene in the form of ice. Set the internal pressure of the freeze dryer to 0.1Pa to 100Pa to sublime the ice. Perform deep dehydration treatment on the freeze-dried butadiene by using 4A molecular sieve. Then place the butadiene in a sealed container and circulate inert gas to replace excess oxygen in the container until the oxygen content drops below the ppm level.

3. The method for preparing an aging-resistant ABS resin according to claim 2, characterized in that: The specific steps of the free radical emulsion copolymerization reaction in S1 are as follows: P2.1: Clean and dry the inside of the reactor, then add 150-300 parts of deionized water into the reactor, and slowly add 0.5-5 parts of polyoxyethylene alkyl ether emulsifier solution into the deionized water, then start the stirring system of the reactor, stir at a speed of 200-500rpm for 10-20 minutes, so that the polyoxyethylene alkyl ether emulsifier is fully dissolved and evenly distributed in the water phase to form a uniform water phase system; P2.2: According to the formula ratio, weigh the pretreated styrene, acrylonitrile and butadiene respectively, and slowly add each monomer into the prepared aqueous phase in the order of styrene, acrylonitrile and butadiene. Then slowly add the potassium persulfate solution into the reactor and continue stirring at a speed of 300-600rpm for 20-30 minutes until the mixture is evenly mixed. P2.3: gradually raise the temperature in the reactor to 60-85°C at a rate of 1-2°C per minute, and adjust the stirring speed of the reactor to 400-800rpm. Continue the reaction for 3-6 hours. During the reaction, take samples regularly for analysis to monitor the conversion rate of the monomer and the molecular weight of the copolymer. P2.4: When the reaction reaches more than 90%, stop heating and gradually cool the reactor to room temperature. After the reaction is completed, open the reactor, use a filter to unload the reaction product, separate the unreacted monomers and impurities to obtain a preliminary purified copolymer emulsion, and then remove excess emulsifier and residual monomers by evaporation or solvent extraction to obtain the ABS resin matrix.

4. The method for preparing an aging-resistant ABS resin according to claim 3, characterized in that: The nanofiller described in S2 is specifically nano-silicon dioxide, nano-calcium carbonate, nano-clay or carbon nanotube.

5. The method for preparing an aging-resistant ABS resin according to claim 4, characterized in that: The specific steps of melt blending described in S2 are as follows: P3.1: Dry the nanofiller at 80-100°C for 4-6 hours, then add the dried nanofiller to the silane coupling agent solution, stir at 50-70°C for 1-2 hours until the mixture is uniformly stirred, and then dry at 120-150°C for 2-4 hours to obtain the surface-treated nanofiller; P3.2: Weigh the treated nanofiller and maleic anhydride grafted polyethylene according to the formula ratio of 5-20% nanofiller to 80-95% maleic anhydride grafted polyethylene, and then pre-mix the treated nanofiller and maleic anhydride grafted polyethylene in a low-speed mixer or high-speed mixer for 10-15 minutes; P3.3: Start the twin-screw extruder and preheat it to 180-220℃. When the temperature of the equipment is stable, add the premix to the feed port and add the ABS resin matrix at a formula ratio of 70-95%. Then the premix and ABS resin are heated and melted in the twin-screw extruder at the same time. P3.4: The twin-screw extruder screw blends the molten premix with the ABS resin matrix at a speed of 100-300rpm for 2-5 minutes until a uniform composite material is formed. The molten composite material is then extruded through the extrusion die of the equipment, cooled to room temperature by air cooling or water bath, and then pelletized by a pelletizer to obtain the final ABS resin particles.

6. The method for preparing an aging-resistant ABS resin according to claim 5, characterized in that: The specific steps of surface treatment of ABS resin described in S3 are as follows: P4.1: Weigh 0.1-0.5% of the mass of ABS resin as hindered phenol antioxidant, and weigh 0.2-1.0% of the mass of ABS resin as hindered amine light stabilizer, and then put the hindered phenol antioxidant, hindered amine light stabilizer and ABS resin particles into a high-speed mixer; P4.2: Mix the hindered phenol antioxidant, the hindered amine light stabilizer and the ABS resin particles by a high-speed mixer at a speed of 1000-3000 rpm for 10-15 minutes. After the mixing is completed, preheat the ABS resin particles to which the hindered phenol antioxidant and the hindered amine light stabilizer are added to 50-80°C; P4.3: Evenly cover the surface of the preheated ABS resin particles with a surface treatment agent of 1-3% by spraying or dipping for 5-10 minutes, and dry the surface-treated ABS resin particles at a temperature of 80-120°C for 1-2 hours.

Citation Information

Patent Citations

  • Preparation method of ageing resistant ABS (acrylonitrile butadiene styrene) resin novel material

    CN108410116A

  • Environment-friendly and efficient water repellent agent and preparation method thereof

    CN111440272A